Potential of known and short prokaryotic protein motifs as a basis for novel peptide-based antibacterial therapeutics: a computational survey - Ruhanen, Heini; Hurley, Daniel; Ghosh, Ambarnil; O'Brien, Kevin T.; Johnston, Catrióna R.; Shields, Denis C. (Frontiers in Microbiology, 2014)
Short linear motifs are functional stretches of protein sequence that are of crucial importance for numerous biological processes by mediating protein-protein interactions. These motifs often comprise peptides of less than ten amino acids that modulate protein-protein interactions. While well characterised in eukaryotic intracellular signaling, their role in prokaryotic signaling is less well understood. We surveyed the distribution of known motifs in prokaryotic extracellular and virulence proteins across a range of bacterial species and conducted searches for novel motifs in virulence proteins. Many known motifs in virulence effector proteins mimic eukaryotic motifs and enable the pathogen to control the intracellular processes of their hosts. Novel motifs were detected by finding those that had evolved independently in three or more unrelated virulence proteins. The search returned several significantly over-represented linear motifs of which some were known motifs and others are novel candidates with potential roles in bacterial pathogenesis. A putative C-terminal G[AG].$ motif found in type IV secretion system proteins was among the most significant detected. A KK$ motif that has been previously identified in a plasminogen-binding protein, was demonstrated to be enriched across a number of adhesion and lipoproteins. While there is some potential to develop peptide drugs against bacterial infection based on bacterial peptides that mimic host components, this could have unwanted effects on host signaling. Thus, novel short linear motifs in virulence factors that do not mimic host components but are crucial for bacterial pathogenesis, such as the type IV secretion system, may be more useful to develop as leads for anti-microbial peptides or drugs.